Relationship of Compliance with Drinking Blood Supply Tablets, Diet and Knowledge about Anemia on the Incident of Anemia - Sri Rahmiyati; Fathurrahman; Rahmani (Jurnal Riset Pangan dan Gizi, 2025)
Anemia is a condition where the level of hemoglobin in the blood is below normal due to a deficiency of essential nutrients, especially iron. The causes of anemia in adolescent girls include low adherence to taking iron supplements (TTD), improper eating patterns, and low knowledge about anemia. This study aims to determine the relationship between adherence to taking iron supplements, dietary patterns, and knowledge about anemia on the incidence of anemia. The type of this research is analytical and observational in nature, using a cross-sectional approach. The research was conducted at SMAN 13 Banjarmasin with a sample of 78 people.The sampling technique used was systematic random sampling. Data analysis used the chi-square test. The research findings revealed that 76.9% of adolescent girls did not adhere to taking iron supplements, 37.2% had a low consumption pattern of iron-rich foods, and 57.7% had good knowledge about anemia. Based on statistical tests, there is a relationship between adherence to TTD consumption (p=0.001), and no significant relationship between a diet high in iron (p=0.584) and knowledge (p=0.305) with the incidence of anemia among students at SMAN 13 Banjarmasin. Teenage girls need to pay attention to a diet high in iron at least 3 times a day and avoid consuming inhibitors at the same time as main meals, and that teachers increase their involvement in supervising the consumption of TTD.